(untitled) - Perkins, Richard J. (America, 1989)
This book provides easy-to understand methods of proper septic practices suited to abroad range of site conditions, and the reasons for using them. Potential problems, both with the system components and the people who regulate septic systems, are described and potential solutions provides.
Keywords: Sanitation,Sewage disposal